Coping de fatores de risco/proteção para a saúde mental de profissionais da saúde durante a pandemia da COVID 19 - Silva, Livia Barreto (2022)
The present dissertation aimed to investigate the mental health of health care professionals working during the COVID-19 pandemic, identifying which coping strategies were used, how they relate with adaptive and maladaptive outcomes for mental health, in addition to identifying which are the factors of risk and protection for the mental health at this population. To this end, two separate studies were carried out, which generated two articles presented here. In Article 1, an integrative literature review was carried out in order to survey what had already been published in terms of data on the mental health of health care professionals, during the COVID-19 pandemic. A search for articles published between the years 2019 and 2021 was carried out in the Pubmed, Scielo and Redalyc databases, using the descriptors “health professionals”, “mental health”, “well-being” and “COVID-19”. 48 publications were selected, following the PRISMA methodology. The results indicate a focus on the mental health of medical professionals, with few studies on other categories, especially psychology. In addition, it is necessary to carry out more interventions, since most of the publications were Literature Reviews. Only 2 studies proposed interventions for these professionals. Finally, most of the publications were carried out in Brazil, which shows a national presence, but it was not possible to compare Brazilian data with international data. Article 2, in turn, consisted of a mixed-method study in order to collect mental health data from Brazilian health professionals, highlighting which coping strategies were used and their individual perception of themselves and the situation in general. Fifty-three professionals participated, most of them female (79%), with a mean age of 34 years (ranging from 23 to 60 years, SD= 10.8). Of these, 17 are physicians (32%), 14 physiotherapists (26%), 11 nursing staff (20%), and 11 psychologists (20%). The study was divided into two stages, the first consists of an online questionnaire with sociodemographic data, Brief Cope Inventory, Meaning-Centered Coping Scale, PERMA Profiler, Depression, Anxiety and Stress Scale (DASS-21), Brief Resilience Scale and Oldenburg Burnout Inventory (OLBI). The second stage consisted of open-ended questions about which strategies the participants used, how they would describe their mental health during this period, how they evaluate political management, etc. The results show that, in general, the participants did not present critical averages for mental disorders. The most used strategies were Active Coping, Positive Reinterpretation and Acceptance; the least used was Behavioral Divestment. Although the statistical data do not point to a worrying degradation for mental health, the qualitative report shows a period of high stress level and many environmental stressors as risk factors. However, some strategies such as distraction and self-care were protective factors for their health. This dissertation makes an important contribution to the understanding of using coping strategies and the demand for change of what are considered adaptive and maladaptive strategies, in addition to the comparison between different moments of the pandemic and what particularities this brought to health professionals. For future research, it is suggested that the instruments be replicated in order to verify a causal relationship between the use of strategies and the protection of mental health, which can be generalized to other contexts and samples in other studies as well.